Issues for an ASEAN charter - Acharya, Amitav (2016)
THE forthcoming ASEAN summit in Kuala Lumpur in December 2005 is likely to appoint an Eminent Person’s Group (EPG) to guide the development of an ASEAN Charter. The Charter is intended as a step towards the establishment of an ASEAN Community by 2020 founded on three pillars – the ASEAN Security Community (ASC), ASEAN Economic Community (AEC) and ASEAN Socio-Cultural Community (ASCC). Does the Charter mark a defining moment, or a new beginning for ASEAN?